2022
DOI: 10.3390/v14050861
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast Inhibits HCoV-OC43 Infection as a Viral Inactivator

Abstract: Coronaviruses (CoVs) consist of a large group of RNA viruses causing various diseases in humans and in lots of animals. Human coronavirus (HCoV) OC43, the prototype of beta-coronavirus discovered in the 1960s, has been circulating in humans for long time, and infection with other emerging strains of beta-coronavirus (SARS-CoV, SARS-CoV-2, and MERS-CoV) can lead to severe illness and death. In this study, we found that montelukast, a leukotriene receptor antagonist, potently inhibited the infection of HCoV-OC43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“…In MST assays, the Kd value of N-NTD and N-17 was similar to that of another N-NTD inhibitor reported by Luan et al, which has been demonstrated to compete with RNA for N-NTD binding [21]. Therefore, N-17 was presumed to block binding between N-NTD and RNA, thereby further preventing the replication and transcription of the viral genome.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In MST assays, the Kd value of N-NTD and N-17 was similar to that of another N-NTD inhibitor reported by Luan et al, which has been demonstrated to compete with RNA for N-NTD binding [21]. Therefore, N-17 was presumed to block binding between N-NTD and RNA, thereby further preventing the replication and transcription of the viral genome.…”
Section: Discussionsupporting
confidence: 79%
“…HCoV-OC43 anti-viral assays were performed according to routine plaque assay procedures, as previously described with some modifications [21,22]. Briefly, BHK-21 cells were seeded in six-well plates for overnight culture.…”
Section: Hcov-oc43 and Sars-cov-2 Anti-viral Assays Thementioning
confidence: 99%
“…One of the classical human β-coronaviruses, HCoV-OC43, was first used to evaluate the antiviral activity by plaque assay. HCoV-OC43 can replicate efficiently in BHK-21 cell, which was used as a host for virus [27] , [28] , [33] . Particularly, at a concentration of 1 μM, the inhibitory rate of ACF and PRF on OC43 reached about 90 %.…”
Section: Resultsmentioning
confidence: 99%
“…The HCoV-OC43 antiviral assay was performed routinely by plaque assay as previously described with slight modification [27] , [28] . Briefly, BHK-21 cells were seeded in 6-well plates and cultured overnight.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, the cells were incubated with fresh DMEM in the presence of serially diluted GC376 and 2% FBS. After culturing 48 h at 37 ℃, cell viability was detected by Cell Counting Kit-8 (CCK8, Dojindo, Japan) as previously described ( Chen et al., 2022 ; Wang et al., 2022 ).…”
Section: Methodsmentioning
confidence: 99%